Variations in culturable bacterial communities and biochemical properties in the foreland of the retreating Tianshan No. 1 glacier - Wu, Xiukun (Braz J Microbiol, 2018)
As a glacier retreats, barren areas are exposed, and these barren areas are ideal sites to study microbial succession. In this study, we characterized the soil culturable bacterial communities and biochemical parameters of early successional soils from a receding glacier in the Tianshan Mountains. The total number of culturable bacteria ranged from 2.19 × 10(5) to 1.30 × 10(6) CFU g(−1) dw and from 9.33 × 10(5) to 2.53 × 10(6) CFU g(−1) dw at 4 °C and 25 °C, respectively. The number of culturable bacteria in the soil increased at 25 °C but decreased at 4 °C along the chronosequence. The total organic carbon, total nitrogen content, and enzymatic activity were relatively low in the glacier foreland. The number of culturable bacteria isolated at 25 °C was significantly positively correlated with the TOC and TN as well as the soil urease, protease, polyphenoloxidase, sucrase, catalase, and dehydrogenase activities. We obtained 358 isolates from the glacier foreland soils that clustered into 35 groups using amplified ribosomal DNA restriction analysis. These groups are affiliated with 20 genera that belong to six taxa, namely, Alphaproteobacteria, Betaproteobacteria, Gammaproteobacteria, Actinobacteria, Bacteroides, and Deinococcus-Thermus, with a predominance of members of Actinobacteria and Proteobacteria in all of the samples. A redundancy analysis showed that the bacterial succession was divided into three periods, an early stage (10a), a middle stage (25–74a), and a late stage (100–130a), with the total number of culturable bacteria mainly being affected by the soil enzymatic activity, suggesting that the microbial succession correlated with the soil age along the foreland.